1972
DOI: 10.1139/v72-063
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism for Hydrolysis of Primary Alkyl Chlorosulfates in Water. The Kinetic Solvent Isotope Effect and the Secondary Deuterium Isotope Effect

Abstract: The temperature coefficients of the enthalpy of activation (AC;) for the hydrolysis of the three chlorosulfates, methyl, ethyl, and 8-chloro, are shown to have values of -50, -55, and -60 cal deg-' mol-'; values in the same range as previously reported for the hydrolysis of the sulfonyl chlorides. The corresponding value for the 8-methoxy isomer was -40 cal deg-' mol-', about the same as found for the p-methoxybenzenesulfonyl chloride. The kinetic solvent isotope effect, however, was significantly lower than r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1972
1972
2003
2003

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In fact, this pattern is shown by published kinetic data for hydrolysis reactions in aqueous solutions as reported by Robertson and co-workers. These data sets also include kinetic data for solvolysis of a range of compounds in water 22-30 and in D 2 O, 22,23,25,31 the TMD of the latter being 284.35 K. The compounds included methyl trifluoroethanoate, succinic and phthalic anhydride, 22 dimethylsulfamoyl chloride, 23 diethyl and methyl(ethyl)sulfamoyl chloride, 24 methanesulfonyl and benzenesulfonyl chloride, 25 methyl chlorosulfate and ethyl chlorosulfate, 27 2-chloroethyl(methyl) sulfide, 28 methyl methanesulfonate 29 and 4-substituted benzenesulfonyl chlorides. 30 Moelwyn-Hughes et al 26 reported rate constants for the solvolysis of 2-chloro-2 methylpropane in aqueous solution at intervals of 1 K from 273.15 to 298.15 K. Novel features in the kinetic data can neither be discerned from isobaric pairs of temperatures nor from around the TMD.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this pattern is shown by published kinetic data for hydrolysis reactions in aqueous solutions as reported by Robertson and co-workers. These data sets also include kinetic data for solvolysis of a range of compounds in water 22-30 and in D 2 O, 22,23,25,31 the TMD of the latter being 284.35 K. The compounds included methyl trifluoroethanoate, succinic and phthalic anhydride, 22 dimethylsulfamoyl chloride, 23 diethyl and methyl(ethyl)sulfamoyl chloride, 24 methanesulfonyl and benzenesulfonyl chloride, 25 methyl chlorosulfate and ethyl chlorosulfate, 27 2-chloroethyl(methyl) sulfide, 28 methyl methanesulfonate 29 and 4-substituted benzenesulfonyl chlorides. 30 Moelwyn-Hughes et al 26 reported rate constants for the solvolysis of 2-chloro-2 methylpropane in aqueous solution at intervals of 1 K from 273.15 to 298.15 K. Novel features in the kinetic data can neither be discerned from isobaric pairs of temperatures nor from around the TMD.…”
Section: Discussionmentioning
confidence: 99%
“…which is reflected ill low substrate \ d u e s (n?) and 111 srnall solvatlon nun~bers (11). i n~g h t be lespons~ble for the abnornlally lalge entrop~es of a c t~~a t l o n characteristic of chlorosulfate solvolysis Solvatlon numbel s reflect the degree of reorgan~zation of solkent molecules necessary in the formation of the transition state: the greater the solvent -reorganizat~on, the more negative mrght AS* be expected to be (27,34).…”
Section: As* Itz Clzlorontljde S O L~o L Y S I~mentioning
confidence: 99%
“…Related mechanistic studies of chlorosulfates have been reported from this as well as other laboratories (10-12). Solvolytic studies of sulfonyl chlorides (1 [3][4][5][6][7][8][9][10][11][12][13][14][15][16] also have a bearing on this work. In Table 1 are presented the data for the conductimetrically determined rates of hydrolysis of ethyl, n-propyl, isobutyl, and neopentyl chlorosulfate in various dioxane-water media at 25°C.…”
mentioning
confidence: 99%